Mineralogical, physical and chemical investigation of compacted Kunigel V1 bentonite in contact with a steel heater in the ABM test package 1 experiment, Äspö laboratory, Sweden. (1st March 2017) - Sasamoto, H.; Isogai, T.; Kikuchi, H.; Satoh, H.; Svensson, D.
In many countries, compacted bentonite is a candidate engineering barrier material for safe disposal of high-level radioactive waste. The Swedish Nuclear Fuel and Waste Management Company (SKB) set up an in situ experiment (the ABM project) to compare the stability of different bentonites under the conditions of exposure to an iron source and to elevated temperature (up to 130°C) at the Äspö Hard Rock Laboratory, Sweden. Results for the Japanese bentonite (Kunigel V1) are summarized in the present study. Mineralogical investigation using X-ray diffraction (XRD) and scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX) suggested no transformation of smectite or neoformed clay phases. However, a distinct change in exchangeable cations of smectite was indicated (i.e. from Na type to Fe type and/or Ca type) in the bentonite in the vicinity of the steel heater. Measurements of hydraulic conductivity and swelling properties suggest that no significant changes occurred in the bentonite even in the vicinity of the steel heater. This is attributed to the limited portion of the bentonite affected by the iron–bentonite interactions and the incomplete ion-exchange reactions. The methylene blue cation exchange capacity and the determination of the exchangeable cations showed that the lateral distribution for these parameters was constant. However, the total exchangeable cation population has changed significantly compared to the initial sample.